4-Hydroxyphenylpyruvate dioxygenase from sea cucumber Apostichopus japonicus negatively regulates reactive oxygen species production. Issue 101 (June 2020) - Liang, Weikang; Zhang, Weiwei; Lv, Zhimeng; Li, Chenghua
Abstract: As a wide distribution molecule, 4-hydroxyphenylpyruvate dioxygenase (4-HPPD) catalyzes the second step in the tyrosine catabolism pathway. This process commonly occurs in all aerobic life forms. The broad distribution of these metabolites suggests that they have an important role in many organisms. A portion of the 4-HPPD homology sequence was also identified in Apostichopus japonicus transcriptome. However, the functional roles of A. japonicus 4-HPPD remain unclear. In the current study, a 4-HPPD homolog was cloned from A. japonicus (designated as AjHPPD ). The nucleotide sequence analysis showed that the open reading frame of AjHPPD was 1149 bp and encoded a 382-amino-acid residue polyprotein with glyoxalase_4 (residues 20–133) and glyoxalase (residues 180–335) domains. The spatial expression analysis revealed that AjHPPD was ubiquitously expressed in all examined tissues with large-magnitude in the respiratory tree and was minimally expressed in coelomocytes. Compared with a control group, the significant increase in transcription of AjHPPD mRNA in the Vibrio splendidus -challenged sea cucumber was 2.10-fold ( p  < 0.01) at 48 h and returned to the normal level at 72 and 96 h. Similarly, compared with a control group, the significant increase in the transcription of AjHPPD mRNA was 3.36-fold ( p  < 0.01) at 24 h after stimulation with 10 mg mL −1 of LPS. On the one hand, silencing AjHPPD in vitro could inhibit the expression of pentose phosphate pathway (PPP) flux enzyme glucose-6-phosphate dehydrogenase (G6PD) at the mRNA level and prevent the clearance of reactive oxygen species (ROS) in sea cucumbers. On the other hand, interference of AjHPPD by using speciﬁc siRNA can result in the signiﬁcant promotion of coelomocyte apoptosis with a 1.61-fold increase in vitro . AjHPPD negatively regulated ROS levels by modulating tyrosine catabolism on AjG6PD expression and coelomocyte apoptosis in response to pathogen infection. Highlights: Complete ORF sequence of 4-hydroxyphenylpyruvate dioxygenase was identified in Apostichopus japonicus. AjHPPD mRNA transcripts could be induced in Vibrio splendidus challenged sea cucumber or LPS exposed coelomocytes. Silencing AjHPPD in vitro could inhibit the expression of glucose-6-phosphate dehydrogenase at mRNA level. Silencing AjHPPD in vitro could prevent the clearance of reactive oxygen species. AjHPPD knockdown by siRNA could accelerate the coelomocytes apoptosis.